Event-Based CMOS Image Sensor with Shared DVS Module for Pixel Area Reduction - Lopes, Tiago; Oliveira, Victor; Oliveira, Fernanda; Gomes, José Gabriel (Symposium on Integrated Circuits and Systems Design (SBCCI); 2020: Anais do XXXIII Symposium on Integrated Circuits and Systems Design, 2020)
In event-based image sensors, each pixel works asynchronously and generates an event whenever a luminance change is detected by the dynamic vision sensor (DVS). The drawback of the event-based image sensors is the amount of circuitry necessary inside the pixel. The proposed imager has the goal of reducing the area of the asynchronous time-based image sensor (ATIS), while maintaining the main advantages of this sensor: high dynamic range and low data rate transfer. In order to reduce the pixel area, we propose sharing the DVS among four capture circuits. The DVS is a complex circuit which comprises a photodiode, two capacitors and 26 transistors. By sharing the DVS, the number of components of a pixel is reduced by 30%. System-level simulations show that sharing the DVS yields little impact in image quality. Electrical simulations results from the ATIS schematic diagram in a 0.35 μm technology are also presented, considering DVS sharing, when all photocurrents of the block are the same and when one of the four photocurrents is different.